Memoirs from Away : a New Found Land Girlhood. - Buss, Helen M. (Wilfrid Laurier University Press, 2006)
How does the imagination entwine the shreds of memory of family, place and culture to root a self in the fluid experience of the present? Daughter, wife, mother, teacher, writer and feminist academic, Helen M. Buss / Margaret Clarke has lived in many parts of Canada and writes from a life of multiple perspectives full of contradictory loyalties and obligations, of opposing histories and identities. For this woman, whose sense of a unified identity is so tenuous that she even writes under two names, writing memoirs becomes the way to bring together the diverse strands of her life. A Newfou.